Mineralogical study of matrix- and groundmass-phyllosilicates, and isolated olivines in Yamato-791198 and -793321: With special reference to new finding of 14 Å chlorite in groundmass - Akai,Junji; Kanno,Jinko (1986)
P(論文) Zoning pattern of the isolated olivine grains in Antarctic C2 (CM2) chondrite Yamato-791198 (Y-791198) and Y-793321 analyzed by EPMA suggests that similar bimodal zoning pattern modes are present in isolated olivine grains in both CM2 and CO3 chondrites (NAGAHARA and KUSHIRO, Mem. Natl Inst. Polar Res., Spec. Issue, 25,66,1982), which may be due to close relations of isolated olivine grains in both CM2 and CO3 chondrites. However, modal ratios of magnesium-rich olivine to iron-rich olivine are different between CM2's and CO3 (Allan Hills-77307). Microtextures of matrix minerals in Y-791198 were observed by means of the Electron Microscope (EM) and the High Resolution Electron Microscope (HREM). The same type of phyllosilicates often accumulates in narrow regions (∿μm). Some olivine grains show corosion-like irregular outlines suggesting that some fluid phase may be responsible for alteration. Under a petrographic microscope, the groundmass phyllosilicates seem to have been derived by alteration. These textural evidences suggest the alteration range from μm-to mm-scales. Four types of phyllosilicates (7A platy, 7A poorly organized tubular, 7A poorly crystallized and 17A mixed layer types) were observed in Y-791198. A 11A layer mineral (tochilinite; MACKINNON and ZOLENSKY, Nature, 309,240,1984) was also observed. These characteristics are the same as those in Murchison and Y-74662. Therefore, these matrix minerals may be common in most of C2 (CM2) chondrites not showing a thermal effect. 14A chlorite was observed in the groundmass of chondrules in Y-791198. There are very distinct differences in the phyllosilicate constituent types between the groundmass and the matrix. This difference may be an important clue to understanding the origin of the two types of phyllosilicates in the matrix and the groundmass. Some possible formation processes were considered. It is evident that alteration did happen in the earlier stage of the solar system. departmental bulletin paper